Algoflora of Bioprides of Bukhara and Comparison of the with the Analogue Flora of the Ponds of Uzbekistan (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The article presents data on the comparative analysis of biological ponds, sewage treatment plants, which according to its climatic, hydrological and physical- chemical conditions of the environment is different from the other ponds. This article discusses the ecological- floral analysis of natural population of algal ponds used as biological ponds - reservoirs, clarifiers